Enhancing nurses’ emotional intelligence: Are tenure prolongation, education and in-service training applicable methods even when not specialized? - Nestor Asiamah (Cogent Business & Management, 2017)
Background/objective: Many health care institutions and employers have begun to realize the need for health professionals’ emotional intelligence to be improved continuously. Education, in-service training and tenure prolongation have been the traditional methods for developing and enhancing competencies in the literature. This study attempts to ascertain whether or not these three traditional methods are applicable for enhancing the emotional intelligence of nurses if not specialized. Design/methodology/approach: A cross-sectional quantitative research design was used in this study. A self-reported questionnaire was used to collect data from 532 nurses in Accra North, who were selected using the simple random sampling method. Confirmatory Factor Analysis was used to test hypotheses. Findings: The resulting model is of good fit at 5% significance level [χ2 = 0.805, p = 0.369]. None of the three methods was found to serve as an effective method when not specialized, though each pair of them is positively correlated. It is concluded that none of the three methods can be used to enhance nurses’ emotional intelligence if not specialized. The need for employers and institutions to design and implement the three methods for the specific purpose of enhancing nurses’ emotional intelligence is therefore worth considering. Originality/value: This study is the first to verify whether or not in-service training, education and tenure prolongation improve the emotional intelligence of nurses when not specialized. Apart from its contributions to the literature, this study is expected to serve as a model for conducting similar studies in future.